2022
DOI: 10.3390/jcm11144222
|View full text |Cite
|
Sign up to set email alerts
|

Key Components, Current Practice and Clinical Outcomes of ERAS Programs in Patients Undergoing Orthopedic Surgery: A Systematic Review

Abstract: Enhanced recovery after surgery (ERAS) protocols have led to improvements in outcomes in several surgical fields, through multimodal optimization of patient pathways, reductions in complications, improved patient experiences and reductions in the length of stay. However, their use has not been uniformly recognized in all orthopedic fields, and there is still no consensus on the best implementation process. Here, we evaluated pre-, peri-, and post-operative key elements and clinical evidence of ERAS protocols, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 190 publications
0
1
0
1
Order By: Relevance
“…Según Salamanna et al, (2022), parte esencial de la cirugía segura es una adecuada historia clínica, que incluya información preoperatoria relevante del paciente para garantizar la calidad del servicio, la práctica profesional y la seguridad del paciente. Es así que, la Organización Mundial de la Salud implementó un registro tipo checklist para los pacientes que ingresan al quirófano, el cual está vinculado a la historia clínica.…”
Section: Resultsunclassified
“…Según Salamanna et al, (2022), parte esencial de la cirugía segura es una adecuada historia clínica, que incluya información preoperatoria relevante del paciente para garantizar la calidad del servicio, la práctica profesional y la seguridad del paciente. Es así que, la Organización Mundial de la Salud implementó un registro tipo checklist para los pacientes que ingresan al quirófano, el cual está vinculado a la historia clínica.…”
Section: Resultsunclassified
“…In future medical work, efforts should be made to popularize ERAS protocol in the field of otolaryngology, so that medical personnel in all departments of otolaryngology are fully aware of the possible clinical benefits of ERAS, which will lead to further implementation and development of ERAS within the perioperative period of CRS patients. It is worth noting that the implementation of a single ERAS element often does not result in a significant clinical benefit, but with the active efforts of multiple teams and multiple elements combined, we’ll reap much more benefits from the synergies [ 65 ]. This implies the importance of teamwork and the need to gain the patient’s understanding.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown each member of the interdisciplinary team collaborates, directly communicates and timely refers patients to each other to optimize their health and wellbeing by addressing patients' medical, surgical, functional and psychological needs concurrently (Rosen et al, 2018). Interdisciplinary teamwork approach to patients in the healthcare systems has been linked to better quality care and improved outcomes, multiple practitioners reduces medical errors, effective and efficient communication within an interdisciplinary team that reduces waiting time for interventions, faster treatment, reduced stalls of management within the team and patients frustrations; and prompt referrals, investigations and test results and reduced opportunity for condition worsening (Rosen et al, 2018), In addition interdisciplinary patients approach has been linked to reduced hospital stay due to timely surgical start times to prevent orthopedics and neurological surgery delays, improved quality care, quicker recovery and reduced average length of patients hospital stay (Salamanna et al, 2022). More so, collaboration and effective and efficient communication for patients care has been associated with patients better quality of life and healthcare workers high rate of job satisfaction (O'Daniel & Rosenstein, 2008).…”
Section: Introductionmentioning
confidence: 99%